2018
DOI: 10.1111/ejss.12742
|View full text |Cite
|
Sign up to set email alerts
|

Soil salinization after long‐term mulched drip irrigation poses a potential risk to agricultural sustainability

Abstract: Summary Prevention of soil salinization is key to agriculture in arid and semiarid regions. Because of the desert climate and extensive demand for irrigation, mulched drip irrigation (MDI) has been practised across Xinjiang, the largest cotton‐planting region in China, since the early 1990s, reaching 2 × 106 ha in 2014. Although MDI can minimize irrigation‐induced soil salinization, long‐term practice of MDI causes salts to accumulate in the root zone and on the bare soil surface between mulches, which leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(50 citation statements)
references
References 22 publications
(49 reference statements)
1
44
0
Order By: Relevance
“…Some studies have suggested that short‐term drip irrigation flushes salts to the deeper subsoil and soil salinity appeared to accumulate in the area far from the tape (Liu, Yang, Li, Yu, & Wang, ; Wang, Yang, & Zheng, ). However, other studies have claimed that long‐term (>5 yr) drip irrigation could induce soil salinization, and caused salts to accumulate in the root zone and on the bare soil surface (Mai et al., ; Wang et al., ). Some suggested that the long‐term use of mineral fertilizers can also lead to the accumulation of salt, while the use of organic fertilizers reduced the degree of soil salinization (Cha‐um & Kirdmanee, ; Walker & Bernal, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that short‐term drip irrigation flushes salts to the deeper subsoil and soil salinity appeared to accumulate in the area far from the tape (Liu, Yang, Li, Yu, & Wang, ; Wang, Yang, & Zheng, ). However, other studies have claimed that long‐term (>5 yr) drip irrigation could induce soil salinization, and caused salts to accumulate in the root zone and on the bare soil surface (Mai et al., ; Wang et al., ). Some suggested that the long‐term use of mineral fertilizers can also lead to the accumulation of salt, while the use of organic fertilizers reduced the degree of soil salinization (Cha‐um & Kirdmanee, ; Walker & Bernal, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that drip irrigation can save 25-60% of irrigation water relative to surface irrigation (Aujla, Thind, & Buttar, 2007;Bashour & Nimah, 2004;Evans & Zaitchik, 2008;Ibragimov et al, 2007). Compared with flood and furrow irrigation, drip irrigation distributes water more evenly through the crop seasons and inhibits deep penetration (Karlberg, Rockstrom, Annandale, & Steyn, 2007;Wang, Fan, & Guo, 2019). In Xinjiang, drip irrigation has been widely used in cotton cultivation, with more than 3 million ha of arable land irrigated using this technology (Xinjiang Statistical Bureau, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the existing research results and referring to the actual situation and historical data of the research area [26][27][28], the intensity and range of various salinization risk sources were summarized, and the risk factors that represent the actual situation of the research area were selected. Considering many factors such as the integrity of the data in the study area and its representativeness, the authors chose the surface temperature, the surface elevation, the surface slope, the surface aspect, the normalized differential vegetation index, the plant senescence reflectance index, the land-use and land-cover change, the surface soil water content, the shallow soil salt content (20-40 cm, g/kg), the shallow soil water content (20-40 cm, %), the deep soil salt content (60-80 cm, g/kg), and the deep soil water content (60-80 cm, %) as risk sources, for a total of 12 factors.…”
Section: Selection Of Risk Sources For Salinizationmentioning
confidence: 99%
“…On the basis of the existing research results and referring to the actual situation and historical data of the research area [26][27][28], the intensity and range of various salinization risk sources were Figure 2. Topographic map of the study area: (a) The DEM data of the study area; (b) the surface aspect of the study area; and (c) the surface slope of the study area.…”
Section: Selection Of Risk Sources For Salinizationmentioning
confidence: 99%
“…However, the absorption of nitrogen by crops is heavily influenced by site-specific conditions. Drip irrigation has a leaching effect on the salt present in the root zone, which can create a good water and salt environment for the root system [21]. Previous studies have examined salt and nitrogen, but most of them have focused on water-salt movement [22] or water-nitrogen coupling.…”
Section: Introductionmentioning
confidence: 99%